Boko Haram: the history of an African jihadist movement - Thurston, Alexander (Princeton studies in Muslim politics, 2018)
Introduction -- The lifeworld of Muhammad Yusuf -- Preaching exclusivism, playing politics -- "Chaos is worse than killing" -- Total war in northeastern Nigeria -- Same war, new actors -- Conclusion